Periodontal soft tissue root coverage procedures: A systematic review from the AAP regeneration workshop (2015)
This paper aims to create a "bridge" between research and practice by developing a practical, extensive, and clinically relevant study that translates evidence-based findings on soft tissue root coverage (RC) of recession-type defects to daily clinical practice. This review is prepared in accordance with the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) statement based on the proposed focused questions. A literature search with no restrictions regarding status or the language of publication was performed for MEDLINE and EMBASE databases up to and including June 2013. Systematic reviews (SRs), randomized clinical trials, controlled clinical trials, case series, and case reports evaluating recession areas that were treated by means of RC procedures were considered eligible for inclusion through the three parts of the study (part I, an overview of the base of SRs; part II, an alternative random-effects meta-analyses on mean percentage of RC and sites exhibiting complete RC; and part III, an SR of non-randomized trials exploring other conditions not extensively evaluated by previous SRs). Data on Class I, II, III, and IV recessions, type of histologic attachment achieved with treatment, recipient- and donor-site anatomic characteristics, smoking-related outcomes, root surface conditions, tooth type and location, long-term effectiveness outcomes, unusual conditions that may be reported during conventional daily practice, and patient-centered outcomes were assessed as well. Of the 2,456 potentially eligible trials, 234 were included. Data on Class I, II, III, and IV gingival recessions, histologic attachment achieved after treatment, recipient- and donor-site anatomic characteristics, smoking-related outcomes, root surface conditions/biomodification, tooth type and location, long-term effectiveness outcomes and unusual conditions that may be reported during conventional daily practice, and patient-centered outcomes (i.e., esthetic, visual analog scale, complications, hypersensitivity, patients perceptions) were assessed. Subepithelial connective tissue (CT)-based procedures and coronally advanced flap plus acellular dermal matrix grafts, enamel matrix derivative, or collagen matrix led to the best improvements of recession depth, clinical attachment level (CAL) gain, and keratinized tissue (KT). Some conditions, such as smoking and use of magnification, may affect RC outcomes. All RC procedures can provide significant reduction in recession depth and CAL gain for Miller Class I and II recession-type defects. Subepithelial CT graft-based procedures provided the best outcomes for clinical practice because of their superior percentages of mean and complete RC, as well as significant increase of KT.